2014
DOI: 10.1039/c4ra01454e
|View full text |Cite
|
Sign up to set email alerts
|

The diverse pharmacology and medicinal chemistry of phosphoramidates – a review

Abstract: Promising examples of the phosphoramidates, which possess antiviral, antitumor, antibacterial, antimalarial and anti-protozoal as well as enzyme inhibitor activity are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 90 publications
(140 reference statements)
0
35
0
Order By: Relevance
“…Furthermore, increasing concern for viral infections such as HCV [100,135,176,177] and herpes virus [56] also motivates research. Because there are numerous reviews focused on prodrugs of nucleotides and nucleoside phosphonates [178184], the following paragraphs focus primarily on other emerging applications in the nucleotide area.…”
Section: Current Applications Of Prodrug Technologymentioning
confidence: 99%
“…Furthermore, increasing concern for viral infections such as HCV [100,135,176,177] and herpes virus [56] also motivates research. Because there are numerous reviews focused on prodrugs of nucleotides and nucleoside phosphonates [178184], the following paragraphs focus primarily on other emerging applications in the nucleotide area.…”
Section: Current Applications Of Prodrug Technologymentioning
confidence: 99%
“…The selection of this particular type of phosphonate prodrug was based on our previous experience which led to an increase of membrane permeability and bioavailability for the antiviral ANPs. 16,18,23,24 In the first step of the one-pot reaction sequence, the cleavage of the phosphonate esters 2 and 3 with Me 3 SiBr in dry pyridine under argon atmosphere forms in situ the corresponding trimethylsilyl esters. In the second step, the reaction of these intermediates with ethyl (or isopropyl for 6j and 7j) (L)-phenylalanine in the presence of 2,2′-dithiodipyridine (Aldrithiol) and triphenylphosphine yielded the corresponding target bisamidates 6a, 6c, 6j and 7a, 7b, 7j and tetra-amidates 8h, 8i and 9h, 9i (Scheme 1).…”
Section: Chemistrymentioning
confidence: 99%
“…16,17 In agreement with the literature, we have observed that the preparation of various types of prodrugs of the parent ANP-based inhibitors can significantly improve the activity in cell-based antimalarial assays. 13,15 As a prodrug of choice, we have selected compounds with a phosphoramidate linkage 18 having two identical amino acid esters attached, to facilitate entry into the cells. Due to the presence of equivalent substituents attached to the phosphorus atom, there are no difficulties associated with prodrug 4 chirality.…”
Section: Figmentioning
confidence: 99%
“…33,34,35 In our SAR-study, the ethyl ester of the natural amino acid, L-phenylalanine, was selected to mask both phosphonate groups of our inhibitors. 36,37 This type of prodrug is more stable than ester prodrugs.…”
Section: Chemistrymentioning
confidence: 99%